Studies of Hydrogen Atom Recombination in Solid Hydrogen Deuteride - Wetzel, C. K.; Lee, D. M.; Sheludiakov, S.; Ahokas, J.; Vasiliev, S.; Khmelenko, V. V. (SPRINGER/PLENUM PUBLISHERS, 2026)
We used the method of electron spin resonance (ESR) to investigate the temperature-dependent recombination rate of H atoms in solid molecular hydrogen deuteride (HD). A 1.5 mu m thick solid molecular HD film was deposited at a rate of 2 monolayer/s, onto a gold surface maintained at T=1.5 K. H and D atoms were accumulated in the film by maintaining radio-frequency electric discharge above the film for 19 days. After further storage of the sample for 48 h, at T < 1 K, the D atom signal vanished. The concentration of H atoms was monitored as the sample was warmed stepwise from 1.1 K to 2.8 K. The recombination rate of H atoms in solid HD was found to be proportional to temperature in this range.